The system of integrated activities evaluation – possibility for successful business processes management - Kučinskienė, Marija; Jakiūnienė, Regina (Buhalterinės apskaitos teorija ir praktika, 2014)
This article examines the system of integrated enterprises activities, as one of the tools for increasing the competitive advantage in global market conditions. As well as, the paper provides the information for understanding the main business processes development tools, which can attract not only current customers, but even new ones. The development of strategic management system is one of the ways for effectiveness and operative activities improvements. This could lead to ensure financial and non-financial objectives in all the enterprises management levels. This corresponds the strategic analytical techniques – the balance scorecard application. The balance scorecard technique connects the strategy with business processes and operations, at the same helping to transfer the vision, mission and strategy to specific aims and tasks set in all the hierarchy levels in the enterprises. The research and practical implementation highlighted the new stage of balance scorecard effectiveness indicators – the system of integrated activities evaluation and their adoption for strategic decisions.